Starożytne centra i peryferia europejskie w perspektywie współczesnych teorii społecznych - Ciesielska, Adriana (Studia Europaea Gnesnensia, 2010)
The paper attempts to apply contemporary social theory to research on ancient societies. The author intends to demonstrate the European economic system as it emerged towards the end of the Roman empire and in the early medieval period. For this purpose the author makes extensive use of Immanuel Wallerstein’s theory of world system.